Organizing Farmer Schools in Solving Embug Pest Problems in Duren Village, Tugu District, Trenggalek Regency - Syahrul Ramadhan; Renny Oktafia; Istikomah Istikomah (Proceedings of The ICECRS, 2020)
This study discusses the organization of farmers to make a farm school about pests. The purpose of this organization is to solve the embug pest problem in the village of Duren, Tugu District, Trenggalek Regency. There are various factors causing unresolved embug pest problems in Desa Duren due to a lack of knowledge and lack of farmer education in eradicating embug pests in his village. This assistance research approach is carried out using the PAR (Participatory Action Research) method, which focuses on involving the community as a full research subject. The steps in the PAR method are conducting initial mapping, building humanitarian relationships, setting research agendas for social change, participatory mapping, determining humanitarian issues, devising movement strategies, organizing communities, launching change actions, building learning centers or community schools, reflection and expand the scale of the movement and support. The strategy used to provide knowledge to farmers on how to eradicate embug pests is divided into 3 stages, namely conducting joint problem analysis then designing participatory scara programs and then designing farmer schools as a forum for farmer education in order to provide farmers with knowledge about eradicating ha and ma embug. Farmer school is one form of critical education offered by Paulo Freire. Education is built on the basis of human critical awareness in understanding social reality. Critical awareness is an awareness that understands social problems due to oppressive relationships, systems and social structures. The Peasant School is proof of the success of the concept of critical education.